THEIA slide and scan : a learning aid intended for children suffering from dyslexia and other learning disabilities. - Evangelista, Dominic Joyce V.
Dyslexia is a kind of life-long disorder characterized by severe difficulties in reading and spell[ing]. Individuals who have dyslexia may have difficulty in organizing thoughts that result to poor verbal and reading skills. After frequently committing unavoidable mistakes due to his deficiency, a child may no longer want to participate in class discussions resulting from low self-esteem. Afraid of committing mistakes yet again, he tends to withdraw from the public. So instead of finding a way to cope with it, he just simply tries to hide his deficiency from others. In this age technology has been part of everyday living; it opens doors and allows dyslexics to demonstrate their knowledge in ways that were unimaginable in the past. To take full advantage of technology, an assistive technology that aids the reading and learning process for the dyslexics is created to improve the quality of their education and ensure that they will achieve excellence in literacy, numeracy and essential life skills.